Heteroplasmy in hair: Differences among hair and blood from the same individuals are still a matter of debate - Paneto, Greiciane G.; Martins, Joyce A.; Longo, Larissa V. G.; Pereira, Gabriella A.; Freschi, Adriana; Alvarenga, Vera L. S.; Chen, Bety; Oliveira, Rogerio N.; Hirata, Mario H.; Cicarelli, Regina Maria Barretto [UNESP] (Elsevier B.V., 2007)
The analysis of mitochondrial DNA (mtDNA) is a useful tool in forensic cases when sample contents too little or degraded nuclear DNA to genotype by autosomal short tandem repeat (STR) loci, but it is especially useful when the only forensic evidence is a hair shaft. Several authors have related differences in mtDNA from different tissues within the same individual, with high frequency of heteroplasmic variants in hair, as also in some other tissues. Is still a matter of debate how the differences influence the interpretation forensic protocols. One difference between two samples supposed to be originated from the same individual are related to an inconclusive result, but depending on the tissue and the position of the difference it should have a different interpretation, based on mutation-rate heterogeneity of mtDNA. In order to investigate it differences in the mtDNA control region from hair hafts and blood in our population, sequences from the hypervariable regions 1 and 2 (HV1 and HV2) from 100 Brazilian unrelated individuals were compared. The frequency of point heteroplasmy observed in hair was 10.5% by sequencing. Our study confirms the results related by other authors that concluded that small differences within tissues should be interpreted with caution especially when analyzing hair samples. (C) 2007 Elsevier B.V.. All rights reserved.
Keywords: mitochondrial DNA; point heteroplasmy; hair shafts; blood; hypervariable regions